Vale of Piranhas territory – PB: advances, discontinuities and dismantling of public territorial development policies - Alves de Oliveira, Aldineide; Cabral Marinho dos Santos, Simone (Geografares, 2020)
In this article, we analyze advances, discontinuities and dismantling of rural territorial policies experienced by rural subjects in the Vale do Piranhas Territory, state of Paraiba. Theoretical and empirical in nature, research was performed with representatives of the government, social organizations and beneficiaries of that Territory. The results showed that territorial development policies were implemented in the region, mainly in the period from 2004 to 2015, contributing to the strengthening of family farming and signaling structural changes in access to land, water, credit and education. However, since 2016, the progress achieved has seriously threatened in the face of a process of demobilization and reduction of policies, actions and programs aimed at territorial development.